Comprehensive Study of Inheritance Law Arrangements: Principles, Heirs, Heirs, and Management of Inheritance Boedel - Iqbal Harry Wibowo; Abdillah Tarigan; Amanda Rahmadhani; Aliyyah Putri Hadianto; Khotibul Umam (ISNU Sumatera Utara, 2025)
Inheritance law is an integral part of the civil law system that regulates the mechanism for transferring assets from a deceased person to their legal heirs. In the context of Western civil law as regulated in the Civil Code (KUHPerdata), the inheritance system used is an individual-bilateral system, namely a system that gives each individual the right to receive an inheritance separately from the paternal and maternal lines. This reflects the principle of justice and independence in obtaining a share of the inheritance based on the blood relationship of both parents. This study aims to comprehensively examine the basic principles of inheritance law in the Civil Code, including provisions regarding heirs, heirs, and the management of inheritance estates. This study uses a normative juridical method, namely by examining the provisions of positive law contained in the Civil Code and relevant legal literature. The results of the study indicate that although the Civil Code prioritizes legal certainty in the distribution of inheritance, its implementation in the field still faces various challenges, especially related to disputes between heirs and the implementation of wills. Therefore, a deep understanding of the principles and structure of inheritance law is important to support a fair and legal inheritance process in society.